Uso de smartphones no ambiente de Terapia Intensiva de um hospital universitário no Triângulo Mineiro - Bino, Lia Vieira (2024)
Smartphones are widely used in healthcare settings, including Intensive Care Units (ICUs), and are recognized as vectors for the transmission of pathogenic microorganisms, as well as potential reservoirs of germs that facilitate the spread of infections. This qualitative study aims to explore the perceptions of healthcare teams about the use of smartphones in hospital settings, considering the risks and dangers associated with handling these devices. The research was conducted in an ICU of a large hospital in the Triângulo Mineiro region, using in-depth interviews with healthcare professionals. The questionnaire, consisting of 29 questions (11 sociodemographic questions and 18 in interview format), revealed that smartphones are frequently used during patient care, even at times that require great attention. Although participants disinfect their devices, they do not follow standardized protocols, which compromises the effectiveness of the process. Smartphones provide quick access to information and facilitate interaction between professionals from different departments and hospitals. However, their constant use can impair the concentration and productivity of healthcare professionals. The study found that, despite guidelines to avoid the use of smartphones in the ICU, professionals continue to use these devices for various purposes, often indiscriminately. Inadequate disinfection of smartphones increases the risk of infection, contradicting prevention measures and compromising patient safety. This study highlights the need for specific disinfection protocols and the development of policies that regulate the use of smartphones in critical environments such as the ICU, aiming to minimize the risk of infection and ensure the safety of immunocompromised patients.